Defining a sustainable overbooking approach in the hospitality industry. (1st January 2013) - Fasone, Vincenzo; Faldetta, Guglielmo
Tourism industry is characterised by a growing uncertainty about volume of demand and relationships with tourists. Hotels often practice overbooking to face uncertainty, seeking to maximise rooms' occupancy rates acting on the reduction of uncertainty on demand. At the same time overbooking is often correlated to an increase of uncertainty in relationships because it is very difficult to predict how different customers might react facing overbooking. This article aims to compare two different overbooking approaches: the traditional overbooking approach and an alternative one, called fair and transparent overbooking, according to which customers are made aware in advance of the possibility of overbooking. The main objective is to understand what are the consequences of traditional overbooking, both positive and negative, and then to figure out if the introduction of a new overbooking formula could alleviate the negative consequences, while maintaining the benefits, making it more sustainable from a social, relational and economic point of view. The theoretical analysis is supported by an empirical survey which aims to verify how overbooking is common, for which reasons is mainly practised by hotels and what are the main benefits and problems. Finally, the survey aimed to explore the possibility of practicing the fair and transparent overbooking.